Practising Gender When Networking: The Case of University–Industry Innovation Projects. Issue 6 (11th June 2015) - Berger, Laura; Benschop, Yvonne; van den Brink, Marieke
<x xml:space="preserve">Abstract</x> This paper gains insight into the role of gender in interpersonal networks, which is largely neglected in research on networking. We do so by exploring the concept of 'practising gender', the spatial‐temporal accomplishment of gender practices, when people build, maintain and exit social networks. The paper is based on a study of male‐dominated technological collaboration projects between universities and industry. Our analysis of observations of project meetings and interviews with project participants demonstrates how people in real time and space draw from culturally available gender practices in their networking with each other. This practising of gender was found to be done largely unreflexively, sometimes through humour, within allegedly trivial activities such as pouring coffee and socializing as well as in critical activities such as composing the network. The exploration of the practising of gender in relation to culturally available gender practices enabled us to examine how those gender practices are reproduced, stretched or challenged when people network. We show how focussing on the dynamic side of gender allows us to get better insight into how gender inequalities in networks are reproduced or countered on the micro‐interactional level.